Hollow nanoparticles synthesized via Ostwald ripening and their upconversion luminescence-mediated Boltzmann thermometry over a wide temperature range - Ran An; Yuan Liang; Ruiping Deng; Pengpeng Lei; Hongjie Zhang (Light: Science & Applications, 2022)
Hollow UCNPs with tunable cavity size were synthesized, which can be used as ratiometric luminescent thermometers over a wide temperature range.